Mycobacterium Growth Inhibition Assay of Human Alveolar Macrophages as a Correlate of Immune Protection Following Mycobacterium bovis Bacille Calmette–Guérin Vaccination - Radloff, Juliane; Heyckendorf, Jan; van der Merwe, Lize; Sanchez Carballo, Patricia; Reiling, Norbert; Richter, Elvira; Lange, Christoph; Kalsdorf, Barbara (Frontiers in Immunology, 2018)
Background In order to eliminate tuberculosis (TB), an effective vaccine is urgently needed to prevent infection with Mycobacterium tuberculosis. A key obstacle for the development of novel TB vaccines is the lack of surrogate markers for immune protection against M. tuberculosis. Methods We investigated growth rates of M. tuberculosis in the Mycobacterial Growth Inhibition Assay (MGIA) as a marker for mycobacterial growth control of human bronchoalveolar lavage (BALC) and peripheral blood mononuclear cells (PBMC) before and after vaccination with M. bovis Bacille Calmette-Guérin (BCG) of healthy adult volunteers. Results Vaccination induced a positive response (p<0.001) to purified protein derivate (PPD) in 58.8% of the individuals in an IGRA-ELISpot. Intra-individual evaluation of the MGIA growth rates before and after M. bovis BCG-vaccination revealed no significant difference in time to culture positivity before and after vaccination in BALC (p=0.604) and PBMC (p=0.199). The magnitude of the PPD-response induced by M. bovis BCG-vaccination did not correlate with growth control in BALC and PBMC (correlation=0.468, 95%CI: -0.016-0.775). Conclusion In conclusion, M. bovis BCG-vaccination-induced mycobacterial-specific cytokine immune response does not result in functional immune control against M. tuberculosis in the MGIA